2020
DOI: 10.1523/eneuro.0326-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Inhibition of Physiological Mirror Activity: An EEG-EMG Study

Abstract: Physiological mirror activity (pMA), observed in healthy human adults, describes the involuntary co-activation of contralateral homologous muscles during unilateral limb movements. Here we provide novel evidence, using neuromuscular measurements (electromyography; EMG), that the amplitude of pMA can be voluntarily inhibited during unilateral isometric contractions of intrinsic hand muscles after informing human participants (10 male, 10 female) about its presence and establishing a basic understanding of pMA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
2
5
1
Order By: Relevance
“…AA during unilateral movements therefore has been interpreted as the consequence of an overload of the “nonmirroring transformation network”, in which excitatory inputs exceed inhibitory inputs reaching ipsilateral M1, resulting in net facilitation (Maudrich et al, 2018; Sehm et al, 2016). However, the results of the present and previous studies (Addamo et al, 2010; Maudrich et al, 2020) show that AA could be suppressed, suggesting that volition can effectively modulate this suppression network. During Suppression trials, an increase in the inhibitory inputs to ipsilateral M1 would overcome excitatory inputs, reducing AA.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…AA during unilateral movements therefore has been interpreted as the consequence of an overload of the “nonmirroring transformation network”, in which excitatory inputs exceed inhibitory inputs reaching ipsilateral M1, resulting in net facilitation (Maudrich et al, 2018; Sehm et al, 2016). However, the results of the present and previous studies (Addamo et al, 2010; Maudrich et al, 2020) show that AA could be suppressed, suggesting that volition can effectively modulate this suppression network. During Suppression trials, an increase in the inhibitory inputs to ipsilateral M1 would overcome excitatory inputs, reducing AA.…”
Section: Discussioncontrasting
confidence: 68%
“…Instead, the data imply a general suppression of AA in at least two hand muscles even though AA feedback displayed to participants was only from non‐target‐ FDI. Participants always performed the Suppression trial after the No Suppression trial (Addamo et al, 2010; Maudrich et al, 2020); learning related to the repeated execution of steadiness task could have also contributed to the reduction in AA (Bologna et al, 2012; Watanabe et al, 2017). However, data from a control experiment in a subsample of seven participants showed that AA was not reduced when participants repeated the steadiness task without suppression, during the same or a subsequent session (No Suppression 1, No Suppression 2 and No Suppression 3: 8.9%, 7% and 9%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of delta wave suppression have taken advantage of the physiological mirror response where motor activity involuntarily occurs in the opposite side of the body when deliberate motor activity like hand gesturing are planned (Maudrich et al, 2020 ). When participants were made aware of this activity and asked to inhibit any involuntary co-activation their directed attention exerted an inhibitory drive on the involuntary motor output, and this suppression was accompanied by increased delta power in frontal areas.…”
Section: Discussionmentioning
confidence: 99%